Vascular Calcification Induced by Chronic Kidney Disease Is Mediated by an Increase of 1α‐Hydroxylase Expression in Vascular Smooth Muscle Cells. (4th May 2016) - Torremadé, Noelia; Bozic, Milica; Panizo, Sara; Barrio‐Vazquez, Sara; Fernandez‐Martín, Jose L; Encinas, Mario; Goltzman, David; Arcidiacono, Maria V; Fernandez, Elvira; Valdivielso, José M
ABSTRACT: Vascular calcification (VC) is a complication of chronic kidney disease that predicts morbidity and mortality. Uremic serum promotes VC, but the mechanism involved is unknown. A role for 1, 25(OH)2 D3 in VC has been proposed, but the mechanism is unclear because both low and high levels have been shown to increase it. In this work we investigate the role of 1, 25(OH)2 D3 produced in vascular smooth muscle cells (VSMCs) in VC. Rats with subtotal nephrectomy and kidney recipient patients showed increased arterial expression of 1α‐hydroxylase in vivo. VSMCs exposed in vitro to serum obtained from uremic rats also showed increased 1α‐hydroxylase expression. Those increases were parallel to an increase in VC. After 6 days with high phosphate media, VSMCs overexpressing 1α‐hydroxylase show significantly higher calcium content and RUNX2 expression than control cells. 1α‐hydroxylase null mice (KO) with subtotal nephrectomy and treated with calcitriol (400 ng/kg) for 2 weeks showed significantly lower levels of vascular calcium content, Alizarin red staining, and RUNX2 expression than wild‐type (WT) littermates. Serum calcium, phosphorus, blood urea nitrogen (BUN), PTH, and 1, 25(OH)2 D3 levels were similar in both calcitriol‐treated groups. In vitro, WT VSMCs treated with uremic serum also showed a significant increase in 1α‐hydroxylase expression and higher calcification that was not observed in KO cells. We conclude that local activation of 1α‐hydroxylase in the artery mediates VC observed in uremia. © 2016 American Society for Bone and Mineral Research.